2015
DOI: 10.1007/s10494-015-9627-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reynolds Number on Turbulent Drag Reduction by Superhydrophobic Surface Textures

Abstract: In turbulent flows over streamwise-aligned superhydrophobic surface (SHS) textures, the percent drag reduction is dependent on Reynolds number. This dependence is examined using direct numerical simulations of channel flow over SHS texture at three bulk Reynolds numbers, Re b = 2800, 6785 and 10975.Simulations of regular no-slip channel flows at the same bulk velocities are also performed for comparison. Changes in the flow due to the SHS texture are examined with particular focus on phase averaged statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 33 publications
6
23
0
Order By: Relevance
“…At low speeds, when the surface was found to be mostly dewetted (i.e. retained plastron appearing silvery bright), the drag ratio decreased with the Reynolds number, consistent with some previous experimental studies (Srinivasan et al 2015) and all numerical studies (Min & Kim 2004;Busse & Sandham 2012;Park et al 2013;Lee, Jelly & Zaki 2015). At high speeds, however, the wetted (dark) areas expanded, negating and eventually overshadowing the drag reduction created by the dewetted…”
Section: Towing Plate and Towing Testssupporting
confidence: 89%
See 1 more Smart Citation
“…At low speeds, when the surface was found to be mostly dewetted (i.e. retained plastron appearing silvery bright), the drag ratio decreased with the Reynolds number, consistent with some previous experimental studies (Srinivasan et al 2015) and all numerical studies (Min & Kim 2004;Busse & Sandham 2012;Park et al 2013;Lee, Jelly & Zaki 2015). At high speeds, however, the wetted (dark) areas expanded, negating and eventually overshadowing the drag reduction created by the dewetted…”
Section: Towing Plate and Towing Testssupporting
confidence: 89%
“…Representing the drag ratio obtainable if the entire SHPo surface retained a proper plastron at all speeds, D c was added in figure 6(a) as hollow symbols connected by dotted lines. These 'projected' data by hypothetically assuming no plastron loss are in agreement with the numerical results that the drag ratio of a SHPo trench surface decreases with Reynolds number (Min & Kim 2004;Busse & Sandham 2012;Park et al 2013;Lee et al 2015). They also suggest that a larger pitch or gas fraction could drop the drag ratio further down in large-scale turbulent boundary-layer tests at high Reynolds numbers, similar to the trend found in small-scale turbulent boundary-layer tests at low Reynolds numbers by Park et al (2014), if the entire SHPo surface could remain properly dewetted.…”
Section: Re Xsupporting
confidence: 85%
“…The plastron loss is accelerated by the high shear of turbulent flows and further exacerbated by the hydrostatic pressure as well as many environmental variables [7] inevitable in open-water tests. For turbulent flows, while numerical studies have shown definite drag reduction and brought insights into the drag-reducing mechanism [9][10][11][12], experimental studies have reported mixed results, varying from substantial to negligible drag reduction, and even drag increase. Figure 1 summarizes the recent experimental studies of SHPo drag reduction in turbulent flows [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Since many different flow facilities are used, we compare the results using the friction Reynolds number on smooth surface Re τ = u τ •δ/ν by estimating it from the flow data in each report, similarly to Gose et al [17], where u τ is the friction velocity, δ is boundary layer thickness, and ν is kinematic viscosity. As a relevant trend for drag ratio, the effect of Reynolds number unveiled by numerical studies [9,10] has been observed in some experiments [15,24,27] but contradicted in some others [13,17,21]. Most importantly, all but one [13] experimental study were performed in a confined flow, e.g., water tunnel, whether internal or external.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation